(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper, to write a survey of face recognition such as, first to provide the review the existing history, second is to describe the technical details like as methods, approchases, algorithms, etc., third is research opportunity in face recognition field. We started from the psychophysical studies that how human being perform that work. Then introduced description of techniques and we tried to explain some pre-processing difficulty and its explanation for the face recognition systems.